The Change in the U.S. Import Demand Function from the 1950s to the 1960s: Reply - Joy, James; Stolen, J. D. (The Review of Economics and Statistics, 1977)
Percival, J., and R. Teach, Spectral Analysis: An Application to the Funds Flow of a Savings Institution, State University of New York at Buffalo, School of Management, Working Paper no. 88 ( 1970). Sargent, T., Rates in the Nineteen-fifties, this REVIEW (May 1968), 164-172. Smith, V. K., and R. Marcis, A Time Series Analysis of Post-Accord Interest Rates, Journal of Finance (June 1972), 589-605.